The Association of Keloid Site with its Histopathological Features: an Analytical Observational Study - Wibisono Nugraha; Muhammad Eko Irawanto; Moerbono Mochtar; Nur Rachmat Mulianto; Novan Adi Setyawan; Nugrohoaji Dharmawan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Keloid is a growth of fibrous tissue in the wound tissue of susceptible individuals. This tissue extends beyond the boundaries of the previous wound. The site of keloids commonly appears on a high-tension area, such as the chest, shoulders, and neck. Histopathologically keloids show thickened the epidermis and the vascularization and infiltration of inflammatory cells in the dermis. Purpose: This study aims to determine the relationship between the site of keloids and the histopathological appearance of keloids. Methods: An analytical observational study was conducted on keloid patients visiting the Dermatovenereology outpatient clinic of Dr.Moewardi Hospital. The sample collection used consecutive sampling techniques Result: The majority of keloid patients are >30 years old (46.4%). Most patients with keloids were female (53.6%). Keloids were mostly found on the chest (25.0%). Tounge-like appearance of the epidermis at the edges of the lesions was mostly on the shoulders and chest (33.3% each, p=0.048); flattened appearance was found on the middle epidermis of the lesions, which were mostly on the ears, shoulders, and upper extremities (22.7% each, p=0.011). Increased vascularity was found in the dermis at the edges of the lesions, especially in the ear and chest areas (31.3% each, p=0.046). Moderate-severe inflammatory infiltrates in the dermis at the edges of the lesions were commonly found on the chest (p=0.04). Conclusion: There is a significant relationship between the site of the lesion and the histopathological appearance of the keloid in epidermal as well as dermal layers.